Manajemen Stres dengan Terapi Musik - Nimah, Lailatun; Afifah, Nur; Maliah, Iin (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2023)
Stress is a state of imbalance between psychological, physiological, and behavior due to the threat of a situation. Chronic illnesses that are suffered and require long treatment can be a stress factor for patients and their families. The purpose of this community service is to reduce the stress felt by patients and their families in experiencing illness and undergoing treatment. The stress management used in this community service activity is music therapy. The goal of therapy is to reduce the aches and pains felt by cancer patients. The results of the service activities show that patients and families who take part in the activity show participants' understanding of: the meaning of stress, signs of symptoms of stress and how to do music therapy.